1964
DOI: 10.1111/j.1748-1716.1964.tb02873.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Nervous Factors Controlling Respiration and Circulation During Exercise Employing Blocking of the Blood Flow

Abstract: During uninterrupted work on the bicycle ergometer the blood flow to the legs was suddenly interrupted by means of blood pressure cuffs. In the period with blocked circulation CO2 was added to the inspired air in such amounts that the alveolar PCO2 was maintained constant. The excess work O2‐uptake decreased up to 50%. The pulmonary ventilation, the pulse rate and the systolic blood pressure showed a steady and considerable increase. The cardiac output remained nearly constant with a tendency to decrease durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
2

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 10 publications
(2 reference statements)
1
34
0
2
Order By: Relevance
“…One of these includes sensitization or greater stimulation of muscle mechanoreceptors (15) and metaboreceptors (13) during work, perhaps exacerbated by conversion from type I (slow twitch, aerobic) to type II (fast twitch, anaerobic) muscle fibres (26,27). Other mechanisms include increased sensitivity of peripheral and central chemoreceptors (20,28,29), and amplification of signals within the central nervous system originating from these several inputs (30).…”
Section: Discussionmentioning
confidence: 99%
“…One of these includes sensitization or greater stimulation of muscle mechanoreceptors (15) and metaboreceptors (13) during work, perhaps exacerbated by conversion from type I (slow twitch, aerobic) to type II (fast twitch, anaerobic) muscle fibres (26,27). Other mechanisms include increased sensitivity of peripheral and central chemoreceptors (20,28,29), and amplification of signals within the central nervous system originating from these several inputs (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, during exercise, the stimulus for this reflex is chemical rather than mechanical in nature because the reflex responses are potentiated when circulation through the working muscle is blocked."' 20 Our experiments with DNP provide direct evidence that this neural reflex could, indeed, be brought about by the metabolic effects of exercise, independently of any increase in muscle movement. The "metabolic receptors" for this reflex are the free endings of small myelinated and unmyelinated fibers (groups III and IV).…”
Section: Discussionmentioning
confidence: 86%
“…Data from some of these reports [23,[36][37][39][40] allowed a gas store pattern estimation to compare with this study and are shown in Table 3. Generalizations from these limited data include (1) an inverse relationship between cuff pressure and O 2 s reduction during inflation, (2) a direct relationship between workload and the increase in O 2 s and reduction in CO 2 s after cuff deflation, and (3) the CO 2 s loss after cuff deflation exceeds the change during inflation and also exceeds the O 2 s gain in recovery.…”
Section: Discussionmentioning
confidence: 99%
“…• Venous O 2 : Content from Fick equation with arterial content and measured at exercise conditions A, B, and C and cardiac output ( ) = 15 L/min at conditions A and C, with 1 L/min reduction during condition B, based on observations during cuff-induced ischemia by Asmussen and Nielsen [23].…”
Section: Total Gas Stores Model With Blood Flow and Volume Redistribumentioning
confidence: 99%